Chaperone Mediated Autophagy Substrates and Components in Cancer - Rios, Javiera; Sequeida, Alvaro; Albornoz, Amelina; Budini, Mauricio (Frontiers in Oncology, 2021)
Chaperone-mediated autophagy (CMA) represents a specific way of lysosomal protein degradation and contrary to macro and microautophagy is independent of vesicles formation. The role of CMA in different physiopathological processes has been studied for several years. In cancer, alterations of the CMA principal components, Hsc70 and Lamp2A protein and mRNA levels, have been described in malignant cells. However, changes in the expression levels of these CMA components are not always associated with changes in CMA activity and their biological significance must be carefully interpreted case by case. The objective of this review is to discuss whether altering the CMA activity, CMA substrates or CMA components is accurate to avoid cancer progression. In particular, this review will discuss about the evidences in which alterations CMA components Lamp2A and Hsc70 are associated or not with changes in CMA activity in different cancer types. This analysis will help to better understand the role of CMA activity in cancer and to elucidate whether CMA can be considered as target for therapeutics. Further, it will help to define whether the attention of the investigation should be focused on Lamp2A and Hsc70 because they can have an independent role in cancer progression beyond of their participation in altered CMA activity.